The effectiveness of Instagram Advertising for Digital Marketing Strategy: Systematic Literature Review - Prahita Sri Rahayuningrat; Gusti Tia Ardiani; Juniar Alisa; Rubiah Sugiarti; Nuryanti Taufik (AIBPM Publisher, 2024)
This systematic literature review study aims to understand the effectiveness of Instagram advertising for digital marketing. It used online data from Google Scholar and Proquest with the keywords